The wawn of digital era in the Archives of Bosnia and Herzegovina - Domazet, Siniša (Moderna arhivistika, 2018)
Instead of the well-known technical listing of the advantages gained by digitizing archival records at the beginning of this paper, the research of the topic took the author, entirely unplanned, in a slightly unexpected direction. Which path brought us to today's needs that modern archives should meet? Was it only one straight direction or multiple simultaneous historical and evolutionary processes, from multiple courses? It was interesting to study and understand how the change in scientific methodologies directly affected archivists and accelerated the need for massive access to archival fonds and what the Archives of Bosnia and Herzegovina can do to keep pace in today's Digital Era.
Keywords: access; database; digitalizacija; digitization; dostop; formati; formats; podatkovne baze; scanning; skeniranje